One‐component waterborne in vivo cross‐linkable polysiloxane coatings for artificial skin. Issue 4 (9th December 2019) - Li, Ping; Zhang, Ailing; Zhou, Shuxue
Abstract: Polysiloxane‐based artificial skins are able to emulate the mechanical and barrier performance of human skin. However, they are usually fabricated in vitro, restricting their diverse applications on human body. Herein, we presented one‐component waterborne cross‐linkable polysiloxane coatings prepared from emulsified vinyl dimethicone, emulsified hydrogen dimethicone, and Karstedt catalyst capsules that were first synthesized by solvent evaporation method. The coating had good storage stability and meanwhile could form an elastic film quickly through merging of silicone oil droplets and subsequent hydrosilylation reaction. It was found that the mass ratio of vinyl dimethicone emulsion/hydrogen dimethicone emulsion (V/H), and the dosage of Karstedt catalyst capsules (K/(V + H)) were critical to the curing time, morphology, and mechanical properties of the coatings. With appropriate values of V/H and K/(V + H), the polysiloxane film had the mechanical performance comparable to that from solvent‐based one. The coating could be topically applied to human skin in vivo and in situ turned into an elastic, invisible thin film with good water resistance. In contrast to those reported polysiloxane materials, the one‐component waterborne polysiloxane coating was nontoxic and convenient for in vivo application on human body, making it be a promising candidate as artificial skin in the fields of cosmetics, medical treatment, and E‐skin. Abstract :